Support forMiranda among police chiefs: A qualitative examination - Payne, Brian K. (American journal of criminal justice, 2000)
The U.S. Supreme Court recently grappled with the question of whether it should overturn the landmark case of Miranda v. Arizona. Abolitionists argued the warnings handcuffed the police and allowed many criminals to go free. Proponents maintained Miranda protected offenders and engendered a certain level of professionalism among police officers. Before the Court decided to uphold Miranda, 95 police chiefs from the Commonwealth of Virginia were surveyed about their perceptions concerning Miranda. While one could categorize many chiefs as conformists who wished to keep the warnings, a significant proportion were innovators who advocated various changes. Reasons for these beliefs and their implications are discussed.